2018
DOI: 10.1111/aor.13089
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Pulsatile Flow With Low Systolic Output From Veno‐Arterial Extracorporeal Membrane Oxygenation Improves Myocardial Recovery After Experimental Cardiac Arrest in Pigs

Abstract: Circulatory failure following cardiac arrest (CA) requires catecholamine support and occasionally veno-arterial extracorporeal membrane oxygenation (vaECMO). VaECMO-generated blood flow is continuous and retrograde, increasing ventricular stroke work. Our aim was to assess the benefit of a device generating a pulsatile vaECMO flow synchronized with the heart rhythm lowering systolic vaECMO output on the left ventricular ejection fraction (LVEF) and pulmonary capillary pressure (Pcap) after CA. This experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Nitric oxide secretion from the endothelium is stimulated by the mechanical shear stress of pulsatile flow acting on vessel endothelium. Synchronized pulsatile ECMO flow with the heart rhythm lowering systolic VA ECMO output on the LV ejection fraction and PCWP after circulatory failure following cardiac arrest (36).…”
Section: Physiological Aspects Of Ecmomentioning
confidence: 99%
“…Nitric oxide secretion from the endothelium is stimulated by the mechanical shear stress of pulsatile flow acting on vessel endothelium. Synchronized pulsatile ECMO flow with the heart rhythm lowering systolic VA ECMO output on the LV ejection fraction and PCWP after circulatory failure following cardiac arrest (36).…”
Section: Physiological Aspects Of Ecmomentioning
confidence: 99%
“…Second, there is no clear definition of pulsatility, although we decided pulsatility by referring to "Extracorporeal Life Support: The ELSO Red Book 5th edition" and previous report. 14 In future, consensus should be determined for pulsatility. Lastly, there may be an error to identify the pulsatility at peripheral arteries, such as a radial artery because a high dose of vasopressor could produce the peripheral artery spasm was developed.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous reports suggested that pulsatile ECMO, which provides physiologic pulsatile pressure, is more beneficial than non-pulsatile ECMO. [12][13][14] The purpose of this study was to investigate favorable predictors for better clinical results that involve post-ECPR care as well as pre-and intra-conditions of ECPR.…”
Section: Introductionmentioning
confidence: 99%
“…This new spiral flow aortic cannula has shown some improvements by reducing approximately 21% of impinging velocity near to the aortic wall, and more than 58% reduction on total force generated as compared to standard cannula. Sebastian Voicu et al 66 of the Assistance Publique -Hôpitaux de Paris, Paris, France, assessed the benefit of a device generating a pulsatile veno-arterial extracorporeal membrane oxygenation (VAECMO) flow synchronized with the heart rhythm lowering systolic VAECMO output on the left ventricular ejection fraction (LVEF) and pulmonary capillary pressure (Pcap) after cardiac arrest (CA). In pigs they compared standard nonpulsatile VAECMO (control) with pulsatile synchronized VAECMO (study) group using a pulsatility-generating device.…”
Section: Support and Membrane Oxygenationmentioning
confidence: 99%